2012
DOI: 10.1016/j.antiviral.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A humanized IgG but not IgM antibody is effective in prophylaxis and therapy of yellow fever infection in an AG129/17D-204 peripheral challenge mouse model

Abstract: Yellow fever virus (YFV), a member of the genus Flavivirus, is a mosquito-borne virus found in tropical regions of Africa and South America that causes severe hepatic disease and death in humans. Despite the availability of effective vaccines, YFV is responsible for an estimated 200,000 cases and 30,000 deaths annually. There are currently no prophylactic or therapeutic strategies approved for use in human YFV infections. Furthermore, implementation of YFV17D-204 vaccination campaigns has become problematic du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
(69 reference statements)
1
24
0
Order By: Relevance
“…Indeed, area-under-the-curve (AUC) analysis showed that there was no reduction in the peak or duration of viremia and there was no evidence that YFV-17D-specific T cells reduced disease symptoms after infection (reviewed in [34]). In contrast, passive transfer of YFV-specific immune serum provides protective immunity against lethal YFV infection in mice [28,35,36], hamsters [37], and rhesus macaques [35]. Together, these studies indicate that neutralizing antibodies are both necessary and sufficient for protection against yellow fever [33].…”
Section: Can Memory T Cells Provide Protective Immunity Against Rementioning
confidence: 99%
“…Indeed, area-under-the-curve (AUC) analysis showed that there was no reduction in the peak or duration of viremia and there was no evidence that YFV-17D-specific T cells reduced disease symptoms after infection (reviewed in [34]). In contrast, passive transfer of YFV-specific immune serum provides protective immunity against lethal YFV infection in mice [28,35,36], hamsters [37], and rhesus macaques [35]. Together, these studies indicate that neutralizing antibodies are both necessary and sufficient for protection against yellow fever [33].…”
Section: Can Memory T Cells Provide Protective Immunity Against Rementioning
confidence: 99%
“…Although cellular immunity plays an important role in clearing primary WNV infection [5-9], memory CD8 + T cells are dispensable if high levels of antiviral antibody are present [7] and vaccine-induced memory T cells may not play a substantial role in controlling flavivirus infection in humans [10]. Moreover, a number of studies using passive immunization have shown that transfer of neutralizing antibodies to naïve animals is sufficient for protection against lethal WNV infection [11-15]. Accordingly, neutralizing antibody titers are generally correlated with protection against disease for licensed flavivirus vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a murine model of disease in mouse strain AG129, which is deficient in α/β- and γ-interferon receptors, peripherally challenged with YF 17D-204 vaccine (Thibodeaux et al, 2012a) and used this model system for evaluation of 2C9-cIgG (Thibodeaux et al, 2012b). Although AG129 mice lack a functional interferon response, they provide a useful model for initial proof of concept studies.…”
Section: Introductionmentioning
confidence: 99%